The first in‐depth exploration of the genome of the engineered bacterium, Gluconobacter thailandicus. (31st May 2021) - Liu, Xiaoxiao; Ali, Afsana; Liu, Chenyi; Liu, Yupeng; Zhang, Pengpai
Abstract: Glycerol is an abundant byproduct of biodiesel production that has significant industrial value and can be converted into dihydroxyacetone (DHA). DHA is widely used for the production of various chemicals, pharmaceuticals, and food additives. Gluconobacter can convert glycerol to DHA through two different pathways, including membrane‐bound dehydrogenases with pyrroloquinoline quinone (PQQ) and NAD(P) + ‐dependent enzymes. Previous work has indicated that membrane‐bound dehydrogenases are present in Gluconobacter oxydans and Gluconobacter frateurii, but the metabolic mechanism of Gluconobacter thailandicus 's glycerol conversion is still not clear. Through in‐depth analysis of the G. thailandicus genome and annotation of its metabolic pathways, we revealed the existence of both PQQ and NAD(P) + ‐dependent enzymes in G. thailandicus . In addition, this study provides important information related to the tricarboxylic acid cycle, glycerol dehydrogenase level, and phylogenetic relationships of this important species.